Conversor bridgeless com reduzida tensão de barramento CC para sistemas de iluminação com LEDs - Holler, Bruno Miguel (2022)
LED lamps have become the main technology used for lig hting. For the correct functioning of these lamps, converters, also called drivers, are necessary. A big problem with these drivers is their lifespan, which is usually shorter than the LED lamp. It is estimated that 50% of the problems in this type of circuit are related to electrolytic capacitors. As a solution to this problem in this work, the study and implementation of a converter topology for LED lamp activation will be carried out. The topology features high performance, power factor correction and reduced bus voltage. This last feature provides the possibility of reducing the size and increasing the useful life due to the lower capacitance required in the DC bus, making it possible to use a metallic film capacitor in it. During the work, the steps of steady-state operation, mathematical modeling and validation through the implementation of a physical prototype will be described. The converter project was carried out to drive a 45W LED module, 90V output voltage and 500mA average output current. The topology is based on a bridgeless single-stage converter integrated into a half-bridge inverter, and charge-pump capacitors will be used to help correct the power factor. A switched capacitor hybrid structure is also used, helping to reduce the bus voltage.